Investigating the Relationship Between Weakness in Trunk Stabilizing Muscles and Lower Back Injuries Among Weightlifters in Baghdad Clubs - Mohammed Abdulsalam Fadel Mahdi, (Musamus Journal of Physical Education and Sport (MJPES), 2026)
This study examined the association between trunk stabilizing muscle weakness and lower back trauma in Baghdad weightlifters in sports clubs. Weightlifting usually leads to lower back injury because of the stress placed on the lumbar spine during training and competitive runs. The research used a descriptive correlational method. The group comprised eight purposively selected weightlifters in Baghdad clubs. Trunk muscle strength was evaluated via Front Plank Test, Side Plank Test, and Biering–Sørensen Test. Lower back injury presence and severity assessment were carried out using an injury recording form and the Visual Analogue Scale (VAS). Results showed a statistically significant inverse relationship between trunk stabilizing muscle strength and lower back injuries, indicating that lower trunk muscle strength was associated with higher injury frequency and severity. The results of the study suggest that trunk strengthening exercises be included in the weightlifting programmes of weightlifters and that trunk stability might be routinely checked to reduce the risk of injury.